Intelligent Monitoring System for Freshwater Lobster Aquaculture based on Wireless Sensor Network - Hendrarini, Nina; YBF, Candra; Wiguna, Raffi (International Journal of Engineering and Technology, 2019)
At this time the need for the nourishment of the people becomes important. Nutrition is supported by providing logistic constraint. A lot of things related to efforts to provide food that have good nutritional value. People’s purchasing power is also an important factor that must be considered. Nutrition is also composed of vegetable or animal protein. Acquisition of animal protein, especially of marine animals are inaccessible to the public because the price is expensive. Lobster is just one example of marine animal that has high protein content. Therefore people pursue cultivation of freshwater lobster. Lobster watchcare is not easy because this animal is sensitive to environmental changes. Therefore this cultivation needs intensive monitoring which is difficult to do manually. As a solution proposed a monitoring system that works automatically. In the making of this monitoring system using prototyping method. By using this monitoring system , the consequences of vulnerability lobster habitat is anticipated. Then in turn will increase productivity levels cultivation of freshwater lobster. The monitoring system uses sensor and microcontroller, the result will sent by wireless communication system